Clinical and instrumental characteristics of osteoarthritis in hyperuricemia - E. A. Taskina; A. M. Lila; L. I. Alekseeva; N. G. Kashevarova; K. M. Mikhailov; A. R. Halmetova; E. A. Strebkova; E. P. Sharapova; N. M. Savushkina; D. M. Kudinskiy; T. A. Raskina; I. B. Vinogradova (Современная ревматология)
Objective: to investigate in a multicentre single-stage study the relationships between hyperuricemia (HU) and clinical, instrumental and laboratory parameters of osteoarthritis (OA).Material and methods. The study included 200 patients aged 40 to 75 years with a definite diagnosis of knee (KN) OA that met ACR criteria, with stage I–III OA by Kellgren–Lawrence. The mean age of the patients was 55.9±10.3 years and the body mass index (BMI) was 29.4±6.2 kg/m2. An individual chart was completed for each patient, including anthropometric parameters, medical history and clinical examination data, visual analogue scale (VAS) assessment of KN pain, WOMAC, patient's general health assessment (GHA) and information on comorbidities. All patients underwent standard radiography and magnetic resonance imaging (MRI) of the KN (WORMS), dual-energy X-ray absorptiometry of the lumbar spine and femoral neck, and laboratory examination.Results and discussion. HU was diagnosed in 57 (28.5) patients when the serum uric acid (UA) level was above 360 μmol/L. Patients were divided into two groups according to the presence or absence of HU. The age of the patients in the two groups was comparable, but they differed significantly in terms of disease duration, BMI, waist and hip circumference, which were greater in the HU group (p <0.05). Statistically significant differences were also found in the assessment of the severity of OA course: there were higher pain indices according to VAS, WOMAC total score and its components (pain and functional impairment, FI), GHA in the HU group. On MRI, osteitis was more common in the medial aspect of the tibia (odds ratio 5.75; 95% confidence interval 1.29–25.6; p=0.03). Patients with HU had higher concentrations of CRP, COMP, leptin, insulin, triglycerides and creatinine (p <0.05 for all values).Spearman correlation analysis confirmed the association between HU and duration and radiological stage of OA, the presence of osteitis in the medial aspect of tibia detected by MRI, pain according to VAS and WOMAC, FI according to WOMAC and GHA (p<0.05).Conclusion. At high UA levels, pain values according to VAS and WOMAC are higher, GHA is worse, and CRP and COMP levels are elevated. MRI shows more frequent osteitis in the medial aspect of the tibia in patients with HU. Deciphering the mechanisms that determine the relationship between HU and OA is important for the development of new methods for the prevention and treatment of these diseases.